Fabrication of a superhydrophobic polyurethane foam and its application for continuous oil removal. (2nd February 2018) - Liu, Hai-Dong; Gu, Bin; Yuan, Wei-Feng; He, Qi
Abstract: A new polyurethane foam with superhydrophobicity and excellent lipophilicity is presented and demonstrated experimentally in this work. The superhydrophobic foam is synthesized by dip coating the polyurethane foam with a mixture solution of silicone resine and silicon dioxide nanoparticles. Its superhydrophobic and oleophilic capacity is characterized and verified via the SEM images, the water contact angle measurement, the adsorption tests and recyclability tests for water and some typical oils. Combining with the vacuum assisted oil-water separation technology (VAST), continuous recovery of oil spill at the lab scale is realized on the new superhydrophobic foam. Moreover, the break through pressure for water penetrating through the superhydrophobic foam is determined experimentally and referred as the maximum operation pressure in the VAST.